Philosophy of John Dewey and his Role in Education: رفاء عبد اللطيف حسن (Al-Academy, 2020)
John Dewey is an American philosopher and psychologist. He is one of the primary figures of the philosophy of pragmatism. He is considered one of its founders and one of the leaders of the philosophy of pragmatism. He is one of the most famous figures of the modern education on the international level. His name is associated with the philosophy of education, because he delved in defining the purpose of education and went on talking about linking the theories with the reality without being subject to the existing system and the inherited traditions no matter how ancient they were. He is the godfather of progressive or gradual education, and he is one of the pioneers who established the experimental school in America in cooperation with his wife at the University of Chicago 1896-1904, and he is a philosopher before being a scientist in the field of education.